From Beginning to End: Perspectives of the Dementia Journey in Northern Ontario*. Issue 1 (29th January 2015) - Gregorio, Deanna Di; Ferguson, Shannon; Wiersma, Elaine
RÉSUMÉ: La recherche sur les soins de la démence continue à se développer, mais peu d'attention est accordée à l'expérience de la démence dans les lieux ruraux et nordiques. Cette étude explore la démence à travers les points de vue des services de santé, les soignants, les membres de la communauté, et les personnes atteintes de démence. Les résultats mettent en évidence la complexité de la prise de conscience et la compréhension de ce phénomène dans des lieux ruraux. La perspective des gens vivants avec une démence, la compréhension des services disponibles et une prise de conscience communautaire, sont essentiels à la prise en charge rural. La nécessité d'accroître les connaissances et l'emphase sur le développement des services de santé et bien-être en milieux ruraux sont discutée. ABSTRACT: Research on dementia care continues to develop, yet little attention has been given to the dementia experience in rural, northern communities. This study explored the dementia journey through the viewpoints of health service providers, caregivers, community members, and people living with dementia. The findings highlight the complexity of dementia awareness and understanding. Sound awareness and knowledge of dementia itself, the community services available, as well as of the perspectives of individuals living with dementia and care partners specifically in rural, northern Ontario are fundamental to quality care and support of individuals with dementia. Practical service implications and the need for greater developments with respect to the awareness and understanding of dementia in rural, northern communities are discussed.